2022
DOI: 10.1002/biot.202200029
|View full text |Cite
|
Sign up to set email alerts
|

High cysteine concentrations in cell culture media lead to oxidative stress and reduced bioprocess performance of recombinant CHO cells

Abstract: Cysteine is considered an essential amino acid in the cultivation of Chinese hamster ovary (CHO) cells. An optimized cysteine supply during fed‐batch cultivation supports the protein production capacity of recombinant CHO cell lines. However, we observed that CHO production cell lines seeded at low cell densities in chemically defined media enriched with cysteine greater than 2.5 mm resulted in markedly reduced cell growth during passaging, hampering seed train performance and scale‐up. To investigate the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…This glucose feeding strategy also promoted cell growth efficiently. Cysteine greater than 2.5 mM with low cell densities resulted in counteracted oxidative stress, but Komuczki et al presented that high cysteine concentration with a higher cell concentration can counteract oxidative stress (Komuczki et al 2022 ). Wang et al reported that an upturn in terms of the product titer was influenced by temperature shifted to 33℃ in 14-day fed-batch culture, and 100% normalized titer was set as the highest titer on day 14.…”
Section: Discussionmentioning
confidence: 99%
“…This glucose feeding strategy also promoted cell growth efficiently. Cysteine greater than 2.5 mM with low cell densities resulted in counteracted oxidative stress, but Komuczki et al presented that high cysteine concentration with a higher cell concentration can counteract oxidative stress (Komuczki et al 2022 ). Wang et al reported that an upturn in terms of the product titer was influenced by temperature shifted to 33℃ in 14-day fed-batch culture, and 100% normalized titer was set as the highest titer on day 14.…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ] While augmented feeding typically extends culture duration, it can simultaneously result in wasteful metabolism and hinder growth when culminating in high osmolality. [ 45–47 ] In light of these findings, recalibrating the feeding strategy is warranted to optimize overall culture performance. [ 48 ]…”
Section: Resultsmentioning
confidence: 99%
“…Entering the production stage, the benefit of IFB can only be established on the premise that the status of cells, such as cell density and viability and cell specific productivity, could be sustained till a desirable advantage in volumetric productivity can be discerned. However, maintaining cell status in such a high density culture appeared to be challenging and cell line dependent (Stepper et al, 2020; Xu et al, 2020a; Yang et al, 2014; Yongky et al, 2019), as many studies have observed that some toxic cellular metabolites, such as lactate and ammonia, and metabolic by‐products like reactive oxygen species (ROS), would exert a chain of deteriorating effects on cellular ecosystem and metabolic disorder (Graham et al, 2021; Handlogten et al, 2018; Komuczki et al, 2022; Pereira et al, 2018; Zhou et al, 2023). Consequently, extensive developmental efforts particularly on media or process optimization were often required to achieve a competitive productivity (Stepper et al, 2020; Xu et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%